Medium term health and quality of life outcomes in a cohort of children with MIS-C in Cape Town, South Africa - Phoya, Frank; Butters, Claire; Spracklen, Timothy F.; Kassa, Hanna L.; van der Ross, Hamza; Scott, Chris; Webb, Kate (Frontiers in Pediatrics, 2025)
Background: Multisystem inflammatory syndrome in children (MIS-C) is a disease that occurs after exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)". Its short-term effects have been documented but little data exist on the longer term effects of MIS-C on the health and quality of life of patients. The objective of this study was to assess the long-term effects of MIS-C on the quality of life (QOL) of children.This study was a descriptive prospective study. We included twenty-four participants with previous MIS-C and twenty children with juvenile idiopathic arthritis (JIA) as a positive comparator group. All children were examined and completed a paediatric quality of life (PedsQL) generic inventory score. This score was used to evaluate the School Functioning, Social, Emotional, and Physical quality of life domains.Results: All participants with previous MIS-C made a full recovery, with no medical complaints, and normal physical examinations after a median of 705 days post acute diagnosis. The PedsQL inventory revealed that 16.7% of the children with previous MIS-C showed a deficit in the physical domain compared to 60% of the children with JIA (p<0.001). 12.5% of the children with previous MIS-C had a deficit in their psychosocial domain which included emotional, social, and educational scores, compared to 40 % of the children with JIA (p=0.035).In a cohort of 24 South African children with previous MIS-C, no medical complications were reported. A small proportion felt a prolonged effect on their QOL even after making a full recovery, although this was not as severe as children with JIA, a known chronic disease that affects QOL. This highlights the need to continue to follow up these patients and offer more comprehensive long-term care.